2019
DOI: 10.1109/tpwrs.2018.2862147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BESS Response on Frequency and RoCoF During Underfrequency Transients

Abstract: Battery energy storage system (BESS) services will be of great help when operating power systems at high renewable energy penetrations. This paper demonstrates the requirements for effective frequency and inertia services. Some system operators currently apply scalars to financially reward improved performance. This paper demonstrates a method of validating and improving these scalars by considering the delay time and ramp time of the BESS. The importance of the method used to measure the rate of change of fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 9 publications
0
57
0
1
Order By: Relevance
“…The UPS systems are fully activated when the system frequency dropped below 49.5 Hz within a period 1.45 s. This ramping in the UPS power corresponds to 0.2% droop response. The total energy delivered to the grid before the frequency reaches nadir takes the form given in (15 This expression indicates that the ameliorating impact on the frequency deviation is directly proportional to additional energy provided during the FFR service before the frequency nadir is reached [37]. It is important to ensure the state of charge (SoC) of the UPS to remain within the upper and lower bands to prolong the battery life time as well as to guarantee the operational safety of the system.…”
Section: ) Methods III -Dynamic Response Through Ups Systemsmentioning
confidence: 99%
“…The UPS systems are fully activated when the system frequency dropped below 49.5 Hz within a period 1.45 s. This ramping in the UPS power corresponds to 0.2% droop response. The total energy delivered to the grid before the frequency reaches nadir takes the form given in (15 This expression indicates that the ameliorating impact on the frequency deviation is directly proportional to additional energy provided during the FFR service before the frequency nadir is reached [37]. It is important to ensure the state of charge (SoC) of the UPS to remain within the upper and lower bands to prolong the battery life time as well as to guarantee the operational safety of the system.…”
Section: ) Methods III -Dynamic Response Through Ups Systemsmentioning
confidence: 99%
“…However, the number of applications for longer times (e.g., 2-5 h) and sizes 2 of 20 up to 500 kW is already significant, and applications for bigger sizes (also in the range 1-10 MW) are increasing. In the transmission system, the positive impacts of BESSs for providing a fast response to frequency deviations [3], mitigating under-frequency transients [4], and being exploited for energy arbitrage [5] have been observed. The integration of BESSs with appropriate control strategies has been shown to be able to improve the frequency stability [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the Australian electricity market, FFR is defined as "any type of rapid active power increase or decrease by generation or load, in a timeframe of less than two seconds, to correct supply-demand imbalances and assist with managing frequency" [2]. There have been several studies of FFR encompassing a wide range of technologies [3][4][5][6]. In one study [6], it was shown that wind generators (WG) can provide IR for a very short duration (~10 s).…”
Section: Introductionmentioning
confidence: 99%